Biomimetic Decoy Inhibits Tumor Growth and Lung Metastasis by Reversing the Drawbacks of Sonodynamic Therapy. Issue 1 (25th November 2019) - Zhao, Hongjuan; Zhao, Beibei; Li, Li; Ding, Kaili; Xiao, Huifang; Zheng, Cuixia; Sun, Lingling; Zhang, Zhenzhong; Wang, Lei
Abstract: Sonodynamic therapy (SDT) shows tremendous potential to induce immunogenic cell death (ICD) and activate antitumor immunity. However, it can aggravate hypoxia and release platelet (PLT)‐associated danger‐associated molecular patterns (DAMPs), which impede therapeutic efficacy and promote tumor metastasis. In order to solve these problems, a biomimetic decoy (designated as Lipo‐Ce6/TPZ@MH ) is constructed to reverse the drawbacks of SDT by loading sonosensitizer chlorin e6 (Ce6) and hypoxia‐activated tirapazamine (TPZ) in the red blood cells–PLTs hybrid membrane (MH )‐camouflaged pH‐sensitive liposome. After administration, the decoy exhibits enhanced cancer accumulation and retention abilities due to the immune escape and specific targeting behaviors by biomimetic surface coating. Upon local ultrasound, Ce6 produces toxic reactive oxygen species for SDT, and the resulting hypoxia microenvironment activates TPZ, which can realize a high‐effective synergistic therapy. Meanwhile, DAMPs‐mediated tumor metastasis is significantly inhibited, because the decoy retains platelet binding functions but is incapable of platelet‐mediated metastasis. In addition, ICD‐mediated strong antitumor immunities further prevent the growth and metastasis of the residual tumors left behind after synergistic treatment. Taken together, this study highlights the potential of using this cascade therapeutic therapy plus biomemitic decoy in one nanosystem to both eliminate melanoma in situ and suppress lung metastasis. Abstract : The cascade synergistic therapeutic therapy plus biomemitic decoy in one nanosystem to reverse the drawbacks of sonodynamic therapy, elicit antitumor immunotherapy, eliminate melanoma in‐situ, and suppress lung metastasis.